Hotels : designer & design (Madrid : Kliczkowski-Asppa, 2001)
W Los Angeles-Westwood / Jon Brouse ; Ballantines Hotels / Sarah Robarts ; Maison 104 / Tolkin & Associates ; Avalon Hotel / Koning Eizenberg ; Ace Hotel / Mallet, Eric Hentz ; The Hotel-Miami / L. Murray Dixon ; Chelsea Hotel / Alan Lieberman ; Hudson Hotel / Philippe Starck ; Camberland Hotel / Zarr Arquitectura ; Design Suites / Ernesto Goransky ; The Prince / Alan Powell ; Ca' Pisani Hotel / Roberto Luigi Canovano ; Gallery Hotel Art / Michele Bönan ; Lady's First / Pia Schmid ; Hotel Bleiche / Huber David Ambrosius ; The Hotel-Lucerne / Jean Nouvel ; Side Hotel Hamburg / Architekten y Matteo Thun ; Blakes Hotel / Anouska Hempel Design ; Hotel Aitana / GCA Arquitectos ; Hotel Portixol / Rafael Vidal ; L’hotel Pergolèse / Réna Dumas ; Hotel Bel-Ami / Christian Lalande ; Myhotel Bloomsbury / Conran Design ; The Hempel / Anouska Hempel Design ; Sanderson Hotel / Philippe Starck
Keywords: ARQUITECTURA HOTELERA; HOTELES; DISEÑO DE INTERIORES; DISEÑO INDUSTRIAL; DISEÑO GRAFICO